1984
DOI: 10.1002/j.1460-2075.1984.tb01814.x
|View full text |Cite
|
Sign up to set email alerts
|

T-DNA of a crown gall tumor is organized in nucleosomes

Abstract: Nucleosomes were isolated from chromatin of suspension cultured cells of Nicotiana tabacum var. White Burley, which were either habituated or transformed by Agrobacterium tumefaciens, strain T37. Chromatin repeat length in both types of tissue was identical and can be estimated to be 195 ± 10 bp. Using Southern transfer of nucleosomal DNA and hybridization with cloned nick‐translated HindIII fragments of pTi C58 we show that the T‐DNA originating from the Ti‐plasmid of A. tumefaciens is organized in nucleosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
4
5
0
Order By: Relevance
“…Our results on general DNase I-sensitivity and nucleosomal organization of 3850-T-DNA confirm and extend our previous data on DNase I-sensitivity and nucleosomal organization of wild-type T-DNA in a tobacco tumor [Schafer et al, 1984;Kahl et al, 19871. They also confirm recent observations [Coates et al, 19871 that TL-and TR-DNA of a n octopine-type tumor as well as T-DNA of a nopaline-type-tumor is organized in "opened" nucleosomes and in a DNase I-sensitive state, irrespective of their actual transcription rate and the methylation of cytosine residues.…”
Section: A Prominent Dnase I-hypersensitive Site Mapssupporting
confidence: 94%
See 1 more Smart Citation
“…Our results on general DNase I-sensitivity and nucleosomal organization of 3850-T-DNA confirm and extend our previous data on DNase I-sensitivity and nucleosomal organization of wild-type T-DNA in a tobacco tumor [Schafer et al, 1984;Kahl et al, 19871. They also confirm recent observations [Coates et al, 19871 that TL-and TR-DNA of a n octopine-type tumor as well as T-DNA of a nopaline-type-tumor is organized in "opened" nucleosomes and in a DNase I-sensitive state, irrespective of their actual transcription rate and the methylation of cytosine residues.…”
Section: A Prominent Dnase I-hypersensitive Site Mapssupporting
confidence: 94%
“…A detailed analysis of the chromatin structure of the various wild-type T-DNA genes, their nucleosomal patterns, their general DNase I-sensitivity, and the occurrence of DNase I-hypersensitive sites in cloned tobacco crown gall tumors incited by Agrobacterium tumefaciens has been described in previous reports [Schafer et al, 1984;Kahl et al, 19871. Similar studies on the relationship between gene expression and chromatin structure were now performed on a modified T-DNA in tobacco plants transformed with the disarmed vector plasmid pGV 3850.…”
Section: Chromatin Structure and Expression Of Modified T-dna In Tranmentioning
confidence: 98%
“…The chromatin conformation of the T-DNA from the HT37#15 tumor is essentially the same as that in the E9 tumor line. The T-DNA can be found in a nucleosome conformation, a result which agrees with a report from Schafer et al (24). They have also found that the ToDNA of a different tumor line incited by the A. tumefaciens strain T37 can be found in nucleosomes.…”
Section: Discussionsupporting
confidence: 81%
“…These conditions yielded DNA greater than 25 Kbp in length and preserved chromatin integrity as assessed by a regular and distinct nucleosome repeat 'ladder' generated upon digestion of isolated nuclei with micrococcal nuclease (MN). The bulk nucleosome repeat lenght of chromatin from maize root and leaf is 175 bp and 190 bp, respectively (data not shown), which is in agreement with that reported for tobacco (27) and other organisms (for review see 16).…”
Section: Dna Purification and Analysissupporting
confidence: 80%